2021
DOI: 10.3390/scipharm89010012
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of the Anti-Proliferative Effects of Galenia africana on Human Skin Cell Lines

Abstract: Malignant melanoma is the major cause of skin cancer-related deaths. Surgery in combination with radiotherapy, immunotherapy or chemotherapy is used to eradicate cancer cells, however, this treatment option is limited by the tolerance of the surrounding healthy tissue. The extracts from Galenia africana have been shown to possess anti-cancer flavonoid compounds and can be a safer and cost-effective alternative treatment. The study aimed to compare the anti-proliferative effects of G. africana on human skin cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Following the collection and extraction process, the HaCaT cell line was utilised to evaluate the anti-proliferative and cytotoxic activity of five plant extracts by the MTT assay followed by FACS analysis with the PI/FD double staining method and qualitative confirmation of viable and non-viable cells with confocal microscopy. Natural products are a source of potential new anti-cancer drugs [42][43][44]. Herein, the results demonstrated that C. colocynthis possesses anti-proliferative activity against HaCaT cells, since it showed a significant decrease in cell proliferation from 24 h onwards, while R. stricta showed a delayed but significant inhibition of cell growth at 120 and 168 h. The IC50 values were determined for both plant extracts for C. colocynthis, with 17.32 and 16.91…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Following the collection and extraction process, the HaCaT cell line was utilised to evaluate the anti-proliferative and cytotoxic activity of five plant extracts by the MTT assay followed by FACS analysis with the PI/FD double staining method and qualitative confirmation of viable and non-viable cells with confocal microscopy. Natural products are a source of potential new anti-cancer drugs [42][43][44]. Herein, the results demonstrated that C. colocynthis possesses anti-proliferative activity against HaCaT cells, since it showed a significant decrease in cell proliferation from 24 h onwards, while R. stricta showed a delayed but significant inhibition of cell growth at 120 and 168 h. The IC50 values were determined for both plant extracts for C. colocynthis, with 17.32 and 16.91…”
Section: Discussionmentioning
confidence: 88%
“…This verifies that the growth inhibition observed in the MTT assay is attributed to the toxicity of C. colocynthis towards HaCaT cells rather than cell death. HaCaT cells have been used previously as a model to determine the cytotoxicity of plant extracts [44]. R. stricta demonstrated significant toxicity towards HaCaT cells at the highest concentration of 200 μg/mL after 24 h. Images taken by CSLM through the PI/FD double staining procedure served as a quantitative confirmation of the viability and cytotoxicity assay, as it revealed extreme morphological changes of HaCaT cells treated with C. colocynthis.…”
Section: Citrullus Colocynthist 1000mentioning
confidence: 99%
“…The cytotoxicity of samples was determined using the trypan blue exclusion method according to Ndlovu et al [36] with slight modifications. The cells were seeded at a density of 5 × 10 4 cells/well in 24-well microplates and grown to attachment overnight.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…G. africana has been used traditionally in the form of pastes, decoctions, and lotions to treat wounds and other skin-related ailments (Ndlovu et al, 2021;Heredia et al, 2022). The bioassay-guided fractionation of the EtOH extract of the leaves of Galenia africana led to the isolation of three known flavonoids, (2S)-5,7,2'-trihydroxyflavanone, (E)-3,2',4'-trihydroxychalcone, and (E)-2',4'dihydroxychalcone, and the new (E)-3,2',4'trihydroxy-3'-methoxychalcone (Mativandlela et al, 2009).…”
Section: Galenia Africanamentioning
confidence: 99%
“…Meanwhile, it was also tested with normal cells, and the results did not affect HaCaT cells. A375 cells after treatment showed nuclear condensation, brightly colored nuclei, and nuclear fragmentation, indicating apoptosis (Ndlovu et al, 2021).…”
Section: Galenia Africanamentioning
confidence: 99%